Neurobehavioral toxicity of total body irradiation: a follow-up in long-term survivors - Peper, Martin; Steinvorth, Sarah; Schraube, Peter; Frühauf, Stefan; Haas, Rainer; Kimmig, Bernhard; Lohr, Frank; Wenz, Frederik; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 2000)
Purpose: Total body irradiation (TBI) in preparation for bone marrow transplantation (BMT) is a routine treatment of hematological malignancy. A retrospective and a prospective group study of long-term cerebral side effects was performed, with a special emphasis on neurobehavioral toxicity effects. Methods and Materials: Twenty disease-free patients treated with hyperfractionated TBI (14.4 Gy, 12 × 1.2 Gy, 4 days), 50 mg/kg cyclophosphamide, and autologous BMT (mean age 38 years, range 17-52 years; age at TBI 35 years, 16-50 years; follow-up time 32 months, 9-65 months) participated in a neuropsychological, neuroradiological, and neurological examination. Data were compared to 14 patients who were investigated prior to TBI. Eleven patients with renal insufficiencies matched for sex and age (38 years, 20-52 years) served as controls. In a longitudinal approach, neuropsychological follow-up data were assessed in 12 long-term survivors (45 years, 23-59 years; follow-up time 8.8 years, 7-10.8 years; time since diagnosis 10.1 years, 7.5-14.2 years). Results: No evidence of neurological deficits was found in post-TBI patients except one case of peripheral movement disorder of unknown origin. Some patients showed moderate brain atrophy. Neuropsychological assessment showed a subtle reduction of memory performance of about one standard deviation. Cognitive decline in individual patients appeared to be associated with pretreatment (brain irradiation, intrathecal methotrexate). Ten-years post disease onset, survivors without pretreatment showed behavioral improvement up to the premorbid level. Conclusion: The incidence of long-term neurobehavioral toxicity was very low for the present TBI/BMT regimen.
Gesehen am 22.03.2022